Індикатори оцінювання моделі повоєнного сталого відновлення прикордонних університетів - Холявко, Наталія Іванівна; Kholiavko, Nataliia; Олифіренко І. С.; Olyfirenko I. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджено систему індикаторів оцінювання ефективності впровадження концептуальної моделі повоєнного сталого відновлення прикордонних університетів України в умовах сталого розвитку та цифрової трансформації. Індикатори згруповано за основними блоками моделі: стратегічно-цільовим, функціонально структурним, цифровізаційним і партнерським. Для кожного блоку визначено ключові напрями оцінювання: стратегічна узгодженість і відповідність Цілям сталого розвитку, ефективність кадрового та управлінського потенціалу, рівень цифрової зрілості університету, розвиненість партнерських зв’язків із громадами, бізнесом та міжнародними інституціями. Зроблено висновок, що запропонована система індикаторів може використовуватися як у внутрішньому моніторингу закладів вищої освіти, так і у зовнішніх процедурах оцінювання їх діяльності на державному рівні. /// EN: The article examines the system of indicators for assessing the effectiveness of implementing a conceptual model of post-war sustainable recovery of Ukrainian borderland universities in the context of sustainable development and digital transformation. The relevance of the topic is determined by the large-scale challenges faced by Ukrainian higher education as a result of russia’s armed aggression: the destruction of educational infrastructure, forced displacement of students and academic staff, depopulation of border areas, decline in economic activity, and high security risks. Under these conditions, universities located in border regions play a special role in recovery processes, as they simultaneously fulfill educational, scientific, cultural, and social missions, becoming important agents of sustainable transformations. The indicators are grouped according to the main blocks of the model: strategic-target, functional-structural, digitalization, and partnership. For each block, the key directions of assessment are defined: strategic alignment and compliance with the Sustainable Development Goals, efficiency of human and managerial potential, the level of digital maturity of the university, and the development of partnerships with communities, businesses, and international institutions. It is substantiated that the system of indicators ensures the achievement of several interrelated goals: increasing transparency and accountability of universities, creating tools for strategic management, forming long-term mechanisms for human capital development, and strengthening the role of universities as centers of local post-war sustainable recovery. Particular attention is paid to the potential of digital technologies (Artificial Intelligence, Big Data Analytics, blockchain, cloud computing, Internet of Things), which enable effective monitoring of progress in achieving the Sustainable Development Goals: SDG 4 (quality education), SDG 9 (innovation and infrastructure), SDG 11 (sustainable cities and communities), and SDG 16 (peace and justice). It is concluded that the proposed system of indicators can be used both for internal monitoring of higher education institutions and in external evaluation procedures at the state level.
Indicators for evaluating the model of post-war sustainable recovery of border universities
Keywords: заклад вищої освіти; сталий розвиток; цифрові технології; Цілі сталого розвитку; прикордонні університети; модель повоєнного відновлення університетів; higher education institution; sustainable development; digital technologies; Sustainable Development Goals; borderland universities; post-war university recovery model